Nóng, ấm, mát and lạnh in Vietnamese and hot, warm, cool and cold in English: A Comparative Study - Van, Hoang Van (VNU Journal of Foreign Studies; Vol 32 No 4, 2016)
Abstract: This article attempts to explore the main features of four adjectives of temperature nóng, ấm, mát, and lạnh in Vietnamese and four corresponding adjectives of temperature hot, warm, cool, and cold in English and to contrast some of their main uses in order to illuminate an important experiential domain of language which is close to the living of man, but does not seem to have received adequate attention in Vietnamese-English contrastive linguistics, in translation studies, and in teaching English as a second/foreign language in Vietnam.